Sinergi Dosen dan Mahasiswa dalam Pemberdayaan Wanita di Desa Koripan, Kecamatan Matesih, Kabupaten Karanganyar - Dimas Rahadian Aji Muhammad; Fanny Widadie; Bambang Sigit Amanto (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2020)
Higher education student is known as agent of change that can play a significant role on the transformation of the social life of a society. However, the idealism of students is often hampered by the availability of funds. On the other hand, someone who works as a lecturer at a higher education has a responsibility to do the three pillars of higher education (Tri Dharma Perguruan Tinggi), one of which is to carry out community service activities. To carry out the community service, a lecturer has many opportunities to obtain funds from various funding bodies. This article discusses the community service activity that was done by implementing a synergy between a group of lecturers and students who are the members of the Food Science Technology Student Association (HIMAGHITA) Universitas Sebelas Maret in the Village of Koripan, Matesih Sub-district, Karanganyar Regency. The purpose of the community service activity is to introduce the processing technology of purple sweet potato and corn and to increase the knowledge of food industry management in the group of women farmers in the region. The community service activity included the introduction of flour-making technology, processing technology of purple sweet potato cookies and corn brownies. Based on the results of monitoring and evaluation, it can be concluded that the synergy of lecturers and students can effectively support the community service activity and the introduction of purple sweet potato and corn processing technology can be well-carried out. In addition, the knowledge of farmer women's groups on the management of home-scale food industry increased after this activity was carried out.